Penerapan Teknologi Dehydrator dan Vacuum Packaging untuk Meningkatkan Efisiensi Produksi Terasi Udang pada Kelompok Perempuan Pesisir Dusun Pilangsari, Kabupaten Kendal - Satsya Yoga Baswara; Alfa Narendra; Togani Cahyadi Upomo; Muhammad Faizal Ardhiansyah; Eko Nurcahya Dewi; Fransiska Fransiska; Fahmi Aska Asharudin; Pipit Ayu Lestari; Indriyani Indriyani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Pilangsari Village in Kendal Regency has an annual shrimp catch potential of 5–10 tons, with part of it processed into shrimp paste by the Coastal Women’s Group consisting of 30 members. The main challenge is the traditional drying process, which takes up to a week and depends heavily on weather conditions, along with ziplock packaging that does not fully seal, leading to rapid quality degradation. This community service activity aims to improve production efficiency through the adoption of appropriate technologies, including a dehydrator and food-grade vacuum packaging. The approach involves coordination, needs assessment, training on equipment use, and ongoing technical support. Results show an expected 80% increase in production capacity and efficiency, along with improvements in skills and product quality. The program aims to reduce weather dependency, extend shelf life, and support sustainable economic independence for coastal communities.